On the Role of Dervishes in the Formation of Town Settlements in Bosnia in the 15th Century - Handžić, Adem (Prilozi za orijentalnu filologiju, 2017)
In this paper the author investigates and explains the pioneering role of dervishes in the formation of settlements and the spreading of Islam in· :Qosnia. [At the beginning of the 15th century in eastern Rumelia they had played a similar and clearly important role.] In regions where the Ottomans settled populations from Anatolia in large numbers (Thrace, Seres, Thessaly and Macedonia) the dervishes and their elders ahis founded hundreds of zaviyes (way-side shelters) which, like inns by the roadside, represented points around which settlements grew up. Although there was no great settling in Bosnia, there is evidence of similar occurrences even there. on the basis of the earliest Ottoman censuses the author throws light on the erection of dervish zaviyes at several points in Bosnia at a time when the process of Islamisation was only just'beginning. Because Islamic mysticism (tasawuf with which the dervishes occupied themselves, represented a higher level of the application of Islam (the philosophy of Islam), it is clear that in the initial stages dervishes did not have anyone to whom they could preach the tasawuf; their zaviyes, as in eastern Rumelia, were essentially wayside inns and shelters. In his paper the author has analysed the origin of seven of these zaviyes in Bosnia: in Sarajevo the origin of Isa beg's zaviye dating from 1462, which, according to the vakifname, was essentially an inn and public kitchen; in Visoko the origin of Ayas Pasha's zaviye in about 1477, at a time when the first households of „new Moslems“ (renegades) had only just come into existence and in Rogatica the zaviye built by a certain dervish Muslihuddin some time before 1489 the first Moslem households were also only just emerging. The origin of the so-called Hamzevi zaviye in about 1519 is examined; it was on the Srebrenica Zvornik road and for a long time was a very important way-side inn. The building of the Bahšibeg zaviye in Zvornik some time before 1530 is also explained; it also had the function of a public kitchen. The origin of another zaviye near Prusac, in western Bosnia, in about the middle of the 16th century at the time of the initialIslamisation in the region, is also analysed. Finally the author discusses the origin of the Skender Vakij settlement in the second half of the 17th century, where the role of dervishes was also evident.